2020
DOI: 10.3390/rs12030565
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Scale Weather Patterns Encountered during Flight Influence Landbird Stopover Distributions

Abstract: The dynamic weather conditions that migrating birds experience during flight likely influence where they stop to rest and refuel, particularly after navigating inhospitable terrain or large water bodies, but effects of weather on stopover patterns remain poorly studied. We examined the influence of broad-scale weather conditions encountered by nocturnally migrating Nearctic-Neotropical birds during northward flight over the Gulf of Mexico (GOM) on subsequent coastal stopover distributions. We categorized night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Our comprehensive modelling of bird stopover distributions across this region supports important seasonal differences in the function of coastal sites. We found birds concentrated near the coastline during spring where they were less influenced by landscape composition, characteristic of fallout to rest (Gauthreaux et al 2006; Lafleur et al ., 2016; Clipp et al ., 2020), while birds stopped further inland during autumn in landscapes with increased forest cover, characteristic of habitat selection for refuelling (Buler and Moore, 2011). When spring weather conditions are favourable, coastal habitats may offer refuge for birds that are young, physiologically stressed, dehydrated or in poor energetic condition incapable of sustained flight (Spengler et al ., 1995; Leberg et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our comprehensive modelling of bird stopover distributions across this region supports important seasonal differences in the function of coastal sites. We found birds concentrated near the coastline during spring where they were less influenced by landscape composition, characteristic of fallout to rest (Gauthreaux et al 2006; Lafleur et al ., 2016; Clipp et al ., 2020), while birds stopped further inland during autumn in landscapes with increased forest cover, characteristic of habitat selection for refuelling (Buler and Moore, 2011). When spring weather conditions are favourable, coastal habitats may offer refuge for birds that are young, physiologically stressed, dehydrated or in poor energetic condition incapable of sustained flight (Spengler et al ., 1995; Leberg et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…While bats cannot be distinguished from birds during movement through the airspace, ‘roost rings’ of bats are visible when they depart en mass for nocturnal flight (Stepanian and Wainwright, 2018). Therefore, we excluded data from areas around the Houston (KHGX) and Corpus Christi (KCRP) radars in Texas with persistent free‐tailed bat ( Tadarida brasiliensis ) roosts (Horn and Kunz, 2008; Clipp et al ., 2020). Mapping the relative density of birds departing stopover habitat among radars requires an instantaneous measure of the density of migrating birds aloft during the onset of nocturnal flight for each sampled night.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Turkey Vultures frequently stopped actively migrating to avoid flying during poor weather conditions, adding to the growing literature recognizing weather avoidance as an important driver of stopover use by migrating birds [ 37 39 ]. Turkey Vultures ceased directed flight quickly in response to high rates of change in several weather variables and resumed migration when conditions improved.…”
Section: Discussionmentioning
confidence: 66%
“…Prior to crossing water bodies, for example, migrants-especially lean individuals-may rest briefly along the coast before relocating inland, presumably to seek more food-rich habitats (Deutschlander and Muheim 2009;Smolinsky et al 2013). In contrast, after crossing, birds may be fat depleted (Moore and Kerlinger 1987), which leads to a high concentration of individuals in coastal habitats (Lafleur et al 2016;Clipp et al 2020;Cohen et al 2021) where they may refuel (Moore et al 2017), take long stopovers (Dossman et al 2016), and move among coastal habitats (Deutschlander and Muheim 2009). Importantly, lean birds are known to gain more mass and take longer stopovers than heavier birds (Moore and Kerlinger 1987;Loria and Moore 1990;Dossman et al 2018) because there may be a minimum fuel load to attain before a bird can move on, depending on the distance that needs to be covered.…”
Section: Introductionmentioning
confidence: 99%